Derivation of Moment Equations for Solutions of a System of Nonlinear Difference Equations Dependent on a Semi-Markov Process - Valeyev, K. G.; Dzhalladova, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We propose a method for the derivation of moment equations for solutions of a system of nonlinear difference equations that depends on a finite-valued semi-Markov process. For systems of linear equations, we compare the results obtained with known ones.